2005
DOI: 10.1002/eji.200425753
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines synergize in the recruitment of circulating neutrophils into inflamed tissue

Abstract: The innate immune response against micro-organisms is mediated by phagocytes, attracted by chemokines and other G protein-coupled receptor (GPCR) ligands. Originally, we observed increased neutrophil migration by the interaction of inflammatory CXC chemokines such as IL-8/CXCL8 and granulocyte chemotactic protein (GCP)-2/CXCL6 with regakine-1, a CC chemokine constitutively present in plasma. We here demonstrate statistically significant synergy between regakine-1 and the neutrophil attractants C5a or IL-8/CXCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 32 publications
2
76
0
Order By: Relevance
“…This process leads to the rapid adhesion of neutrophils to the vascular endothelium and the rapid decrease in levels of circulating neutrophils. This decrease in circulating leukocytes is normally due to leukocyte rolling movement along the vessel wall and the subsequent solid adhesion to the endothelial cells and migration into tissues (28). Thus, we investigated the effect of VAMP8 in the recruitment and activation of acute inflammatory leukocytes in vivo in C5a-induced systemic and localized inflammatory models, and showed that, following C5a i.v.…”
Section: Discussionmentioning
confidence: 99%
“…This process leads to the rapid adhesion of neutrophils to the vascular endothelium and the rapid decrease in levels of circulating neutrophils. This decrease in circulating leukocytes is normally due to leukocyte rolling movement along the vessel wall and the subsequent solid adhesion to the endothelial cells and migration into tissues (28). Thus, we investigated the effect of VAMP8 in the recruitment and activation of acute inflammatory leukocytes in vivo in C5a-induced systemic and localized inflammatory models, and showed that, following C5a i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that SDF-1 may participate in the recruitment of neutrophils in arthritis (41)(42)(43)(44) and peritonitis (45). Interestingly, SDF-1 expression has also been implicated in the trafficking of myeloid progenitors during injury and inflammation to the liver (58,59) and the peritoneum (60), suggesting that the same chemokine interactions that maintain neutrophils and their precursors within the marrow (29, 38 -40) may be effective in recruiting these cells to extramedullary sites.…”
Section: Discussionmentioning
confidence: 98%
“…How the CXCR4/ SDF-1 axis might participate in the development of inflammation is poorly understood, but several reports support a role for this pathway in the tissue migration of leukocytes, including neutrophils, in animal models of arthritis (41)(42)(43)(44) and peritonitis (45). A role for SDF-1 in lung inflammation has been suggested by animal models of asthma in which a CXCR4 blockade attenuates both the lymphocyte and eosinophil responses and reduces airway hyperreactivity (46,47).…”
Section: A Cute Lung Injury (Ali)mentioning
confidence: 99%
“…35,36 Thus, whether blocking C5a affects the recruitment of neutrophil/macrophages into inflamed colons, thereby dampens inflammatory responses was addressed. Because complement activation represents an early event during TNBS colitis as described above, colon tissues from anti-C5a-treated and control mice were isolated at 4 h, 24 h, and 4 days after colitis induction and neutrophil/macrophage infiltrates were examined.…”
Section: Blockade Of C5a Activity Restrains Infiltration Of Polymorphmentioning
confidence: 99%